2009
DOI: 10.3947/ic.2009.41.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever Mimicking Acute Appendicitis: A Case Report

Abstract: We experienced a case of enteritis mimicking acute appendicitis in Dengue fever. This is the first case report of such complication in Korea. A 36-year-old man presented with fever and abdominal pain after a trip to the Philippines. He complained of severe pain on the right iliac fossa region. Complete blood cell count showed thrombocytopenia with leucopenia. Computed tomogram (CT) of abdomen and pelvis revealed a normal appendix. Dengue fever was confirmed by IgM capture enzyme-linked immunosorbent assay agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Supplemental Table S1 outlines the reports of acute appendicitis in dengue. [39][40][41][42][43][44][45][46] Six of the eight patients were male. Common clinical presentations include fever, abdominal pain mainly in the right lower quadrant, and tenderness.…”
Section: Common Causes Of Acute Abdomen In Dengue Infectionsmentioning
confidence: 99%
“…Supplemental Table S1 outlines the reports of acute appendicitis in dengue. [39][40][41][42][43][44][45][46] Six of the eight patients were male. Common clinical presentations include fever, abdominal pain mainly in the right lower quadrant, and tenderness.…”
Section: Common Causes Of Acute Abdomen In Dengue Infectionsmentioning
confidence: 99%
“…The countries with relatively low incidence of dengue, such as Taiwan and Singapore, showed severe dengue rates of less than 1%. In Korea, national surveillance system has not reported the incidence of severe dengue, but clinical case study reported a few cases of severe dengue (4344). …”
Section: Imported Cases In Koreamentioning
confidence: 99%
“…Published literature cumulatively report 21 cases of DF presenting as AA, and six patients have undergone appendicectomy. [1][2][3][4] Microscopic evaluation of these specimens showed lymphocytic infiltration, lymphoid hyperplasia or normal microscopy. None of these patients had histological evidence of acute appendicitis and this patient is probably the first to have microscopic evidence of supurative AA.…”
Section: Discussionmentioning
confidence: 97%
“…Published literature provides limited number of reports of acute abdominal problems mimicking DF. [1][2][3][4] Acute appendicitis is a common condition which can get complicated with perforation, peri-appendicial abscess formation, peritonitis and rarely death. [5] We report the experience with an adolescent presented as having AA which was confirmed peri-operatively as well as histologically, who also had evidence of dengue hemorrhagic fever (DHF) during post-operative period.…”
Section: Introductionmentioning
confidence: 99%